1988
DOI: 10.1021/ac00175a019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selenium metabolites in biological fluids using instrumental and molecular neutron activation analysis

Abstract: The dispersion coefficient (D) Is the most popular peak descriptor In flow Injection analysis (FIA). Yet this concept of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…They were also the first to report TMSe in normal human urine (i.e., without selenium supplementation). The data, however, were variable; in one report (25 ) they claimed that TMSe constituted ϳ30% of the total selenium in normal urine, whereas in two other very similar studies (26,28 ), they reported up to 90% TMSe in normal urine.…”
Section: Work Carried Out In the 1980s: Tmse Consolidatedmentioning
confidence: 98%
See 2 more Smart Citations
“…They were also the first to report TMSe in normal human urine (i.e., without selenium supplementation). The data, however, were variable; in one report (25 ) they claimed that TMSe constituted ϳ30% of the total selenium in normal urine, whereas in two other very similar studies (26,28 ), they reported up to 90% TMSe in normal urine.…”
Section: Work Carried Out In the 1980s: Tmse Consolidatedmentioning
confidence: 98%
“…Blotcky and coworkers (25,26,28 ) were especially conspicuous in this area with several publications focusing on determining TMSe with use of neutron activation analysis for detection. They were also the first to report TMSe in normal human urine (i.e., without selenium supplementation).…”
Section: Work Carried Out In the 1980s: Tmse Consolidatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its cationic nature, TMSe + is preconcentrated and separated, usually from inorganic selenium species, on the cationexchange columns. 18,31,34 The high resolution obtained by HPLC permits a clear separation of TMSe + from inorganic selenium and also from other organoselenium compounds. 28,29,32,35 Reversed-phase partitioning and ion exchange chromatography have been applied.…”
Section: Trimethylselenonium Ionmentioning
confidence: 99%
“…31,34,[41][42][43] Organoselenium species (other than TMSe + ) adsorbed on Amberlite XAD-2 resin at pH 8 were classified as neutral and basic forms, while those absorbed at pH 3 were classified as acidic. 31 As the acidic forms dominated in lake water samples, it was concluded that most of these compounds were selenium-containing humic substances.…”
Section: Selenoamino Acidsmentioning
confidence: 99%